Linear and nonlinear active feedback controls for vortex-induced vibrations of circular cylinders. (June 2014) - Mehmood, A; Abdelkefi, A; Akhtar, I; Nayfeh, AH; Nuhait, A; Hajj, MR
We consider the problem of suppressing oscillations of an elastically mounted rigid cylinder undergoing vortex-induced vibrations by linear and nonlinear active velocity feedback controllers. Each controller relies on an actuator, which imparts an opposing force to the cylinder motion, thereby reducing its high-amplitude oscillations. A strongly coupled fluid–structure numerical model is used to solve the fluid–structure interaction equations. The results show that the choice of the active feedback controller depends on the allowable controlled amplitude of the cylinder. It is found that a cubic velocity feedback controller is more efficient than its linear velocity counterpart when very small controlled amplitudes are desired.